Cost Production Evaluation and Effect of Lactic Acid Bacteria (Lactobacillus plantarum) as Starter with Different Molasses Addition - Bachruddin, Zaenal (2015)
This research aims to determine the level of molasses addition to the quality of lactic acid bacteria (LAB) as starter and to calculate cost production of the starter for silage fermentation. By conducting this study, it will be a feasible consideration in utilization of the LAB production by farmers. The variables of the starter quality were the change of pH, lactic acid production, total carbohydrates, total dry matter, total organic matter, and fermentation weight during fermentation. This research used the lactic acid bacteria (Lactobacillus plantarum) which inoculate as much as 5% of the rice bran media. It incubated the bacteria at room temperature for seven days. The treatments were the addition of molasses with concentration of 0% (T0M), 1% (T1M), and 2% (T2M). The result of the study shows that the addition of molasses at different levels and fermentation time are significant (P<0,05) for the pH and weight of fermented rice bran, but it does not give significant effect on lactic acid production, total carbohydrate, levels of dry matter, and levels of organic matter. The treatment of 2% molasses and five days fermentation were the best treatment due to the lowest pH obtained was 3,81. The cost production of the starter is Rp 11,780 per kilogram, thus it increases the total cost production at 24.06%. Starter production by farmers is not yet feasible because farmers are only able to anticipate the increase in the total livestock cost production of 18.47%.